Ageing, solidarity and social protection : time for progress towards equality (UN ECLAC SantiagoCL, 2012)
Summarises the Report on application of the Brasilia Declaration and the Regional Strategy for the Implementation in Latin America and the Caribbean of the Madrid International Plan of Action on Ageing.
Bibliography: p. 85-91.